A SMALL-ANGLE NEUTRON-SCATTERING INVESTIGATION OF SHEAR-ALIGNED HEXAETHYLENEGLYCOLMONOHEXADECYLETHER (C16E6) MICELLES AS A FUNCTION OF TEMPERATURE - Cummins, P; Hayter, J; Penfold, J; Staples, E (1987)
A SANS experiment on hexaethyleneglycolmonohexadecylether micelles subjected to an orienting shear flow has indicated that, as the cloud point is approached, there is a concomitant reduction in micelle rod length. This result is in accord with recent viscosity data and provides evidence for interaction-dominated clouding. © 1987.